Effect of RRA heat treatment on corrosion and mechanical properties of AA7075. Issue 11 (24th May 2019) - Özer, Gökhan; Karaaslan, Ahmet
Abstract : In this study, a retrogression process (R) has been applied to AA7075 at 180, 240, and 370°C for 15, 30, 90, and 120 min. After the retrogression, reaging treatment (RA) was reapplied with T6 conditions (120°C for 24 hr). The effect of different temperatures and time periods of retrogression and reaging temper on exfoliation corrosion (EXCO) of the AA7075 is examined. The EXCO solution was prepared in accordance with the ASTM G34‐01 standard and the samples were kept in the solution for 48 hr. Susceptibility of the alloy to EXCO was determined by weight loss detection, macro and microstructure studies, scanning electron microscope, transmission electron microscope, and energy dispersive X‐ray analyses. The mechanical properties of aged samples were determined by hardness, tensile tests, and fractography. Abstract : A retrogression process (R) has been applied to AA7075 at 180, 240, and 370°C for 15, 30, 90 and 120 min. After the retrogression, reaging treatment was reapplied with T6 conditions (120°C for 24 hr). The effect of different temperatures and time periods of retrogression and reaging temper on exfoliation corrosion of the AA7075 is examined.